The bad omens and luck as constitutive elements of death in Fabla salvaje and the short story «Cera» from Escalas, by César Vallejo - Dominguez Chincha, Gustavo Reynaldo (2023)
This article analyses two texts by César Vallejo: Fabla salvaje and the short story «Cera» by Escalas. In the novel Fabla salvaje, it will be observed how a peak stage is represented: the moment in which the mirror is broken, and from it, the importance of luck and bad omens in the construction of the text will be shown. Likewise, in the story «Cera», we will show an ordered sequence of bad omens that give way to the presence of death. Thus, both the novel and the story have in common the bad omens and the presence of luck as elements that bring with them the possibility of death. In this sense, it is necessary to show the link between these elements, in both texts, and death itself. In other words, the presence of death cannot exist without first having been tacitly or expressly enunciated by different marks in Vallejo’s work.